2014
DOI: 10.1177/1471301213520172
|View full text |Cite
|
Sign up to set email alerts
|

What is the current state of care for older people with dementia in general hospitals? A literature review

Abstract: This paper summarises a literature review focusing on the literature directly pertaining to the acute care of older people with dementia in general hospitals from 2007 onwards. Following thematic analysis, one overarching theme emerged: the consequences of being in hospital with seven related subthemes. Significantly, this review highlights that overall there remains mostly negative consequences and outcomes for people with dementia when they go into general hospitals. Although not admitted to hospital directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
379
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(392 citation statements)
references
References 59 publications
11
379
0
2
Order By: Relevance
“…Seven 72,92,102,125,132,148,162 were qualitative studies, one 107 was a mixed study including a review and a qualitative study, three 93,99,153 were reviews and two 20,94 were questionnaire studies. Three studies 20,94,102 focused on people with dementia and diabetes, two 72,93 focused on those with dementia and VI, one 89 looked at those with dementia and deafness, one 92 focused on those with dementia and cancer, two 148,153 looked at family carers' views on medication management and four 99,107,125,132 looked at the needs of people with dementia in general hospitals. Literature on the experiences of older people with dementia in acute general hospitals has highlighted shortcomings in the care provided, the attitudes and training of staff, and the physical environment and problems with care cultures.…”
Section: Views and Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven 72,92,102,125,132,148,162 were qualitative studies, one 107 was a mixed study including a review and a qualitative study, three 93,99,153 were reviews and two 20,94 were questionnaire studies. Three studies 20,94,102 focused on people with dementia and diabetes, two 72,93 focused on those with dementia and VI, one 89 looked at those with dementia and deafness, one 92 focused on those with dementia and cancer, two 148,153 looked at family carers' views on medication management and four 99,107,125,132 looked at the needs of people with dementia in general hospitals. Literature on the experiences of older people with dementia in acute general hospitals has highlighted shortcomings in the care provided, the attitudes and training of staff, and the physical environment and problems with care cultures.…”
Section: Views and Experiencesmentioning
confidence: 99%
“…Literature on the experiences of older people with dementia in acute general hospitals has highlighted shortcomings in the care provided, the attitudes and training of staff, and the physical environment and problems with care cultures. 99,107,125 Poor communication is a major barrier to the provision of good care for people with dementia and a comorbid health condition. 72,99,107 Practitioners reported that they found it difficult to communicate with PLWD and communication difficulties were compounded when PLWD had additional comorbidities that made communication difficult, such as hearing loss or sight loss.…”
Section: Views and Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of evidence Hanson (2014) found that while many variables contribute towards nurses' attitudes towards older people, studies indicate a strong correlation between negative attitude and insufficient knowledge. Similarly Dewing and Dijk (2014) highlight that poor outcomes for people with dementia in acute hospitals result from a tension between prioritising medical treatment versus the delivery of person-centred dementia care, exacerbated by the fact there is insufficient understanding of what person-centred care is and a lack of staff knowledge and skills to deliver such care. This is supported by Nolan (2006) who found acute hospital nurses in Ireland expressed a desire to care for people with dementia in a person-centred way, but lacked the knowledge to base such care on.…”
Section: Introductionmentioning
confidence: 99%
“…One quarter of hospital beds in the UK is estimated to be used by persons with dementia over the age of 65 (Alzheimer Society, 2009). However, the quality of dementia care in these settings is not optimal (Dewing & Dijk, 2014) and can be challenging (Clissett, Porock, Harwood & Gladman, 2013). Alzheimer Society UK (2009) reported that persons with dementia in hospitals stay longer than other patients without dementia, during which time their physical and cognitive status deteriorates whilst long-term institutionalization and the use of anti-psychotic medication becomes more likely.…”
Section: Introductionmentioning
confidence: 99%